+0

# Factor completely. 3x^2+7x-6

0
1
1207
1

3x^2+7x-6   Factor completely.

a. (x-6)(3x+1)

b. (x-3)(3x+2)

c. (x+3)(3x-2)

d. (x+6)3x-1)

Jul 16, 2017

#1
+7347
+1

3x2 + 7x - 6

Multiply the  3  and  -6  together to get  -18 .

What two numbers add to  7  and multiply to  -18  ? →  +9  and  -2

So...we can split the middle term like this...

=  3x2 + 9x - 2x - 6            Now factor a  3x  out of the first two terms.

=  3x(x + 3) - 2x - 6            Now factor a  -2  out of the last two terms.

=  3x(x + 3) - 2(x + 3)         Now factor a  (x + 3)  out of both remaining terms.

=  (x + 3)(3x - 2)

Jul 16, 2017

#1
+7347
+1

3x2 + 7x - 6

Multiply the  3  and  -6  together to get  -18 .

What two numbers add to  7  and multiply to  -18  ? →  +9  and  -2

So...we can split the middle term like this...

=  3x2 + 9x - 2x - 6            Now factor a  3x  out of the first two terms.

=  3x(x + 3) - 2x - 6            Now factor a  -2  out of the last two terms.

=  3x(x + 3) - 2(x + 3)         Now factor a  (x + 3)  out of both remaining terms.

=  (x + 3)(3x - 2)

hectictar Jul 16, 2017